An uncommon cause of ischemic stroke at a young age: a case report - Mendes, Sofia (2024)
Introduction: Stroke is the main cause of death and disability in Portugal. Primary cardiac tumors are rare, most are benign, and auricular myxoma is the most common of them all. This type of tumor is more common in young women, and it has a variable clinical presentation, depending on the location, size, and mobility of the mass, and can lead to cardioembolic phenomena, such as stroke. Treatment is surgical and, if detected early, the prognosis can be favorable. Case description: We describe the case of a 37-year-old woman, with a history of ischemic stroke considered idiopathic at the age of 22 years old, with left hemi-hypoestesia, vision changes, decreased muscle strength in the left upper limb and changes in gait, with evidence of right thalamocapsular ischemic injury on computed tomography and cranioencephalic magnetic resonance imaging. The transthoracic echocardiogram revealed a left auricular mass suggestive of myxoma, which was confirmed by a transesophageal echocardiogram and subsequently underwent surgical resection and histological confirmation. Comment: If a cardiogenic cause is suspected, an echocardiogram should be performed promptly. Myxoma-type cardiac tumors have a specific treatment indication, which is surgical resection, with a low risk of recurrence of cerebrovascular events during follow-up. This case highlights the importance of complementary studies in stroke. On the other hand, the case also demonstrates the importance of the coordination that must exist between primary and secondary healthcare, particularly cardiology, for the detection and management of pathologies such as auricular myxoma and ischemic stroke.